2019
DOI: 10.48550/arxiv.1911.09651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-weight modules over the super-BMS$_3$ algebra

Abstract: In the present paper, a class of non-weight modules over the super-BMS 3 algebras S ǫ (ǫ = 0 or 1 2 ) are constructed. These modules when regarded as S 0 -modules and further restricted as modules over the Cartan subalgebra h are free of rank 1, while when regarded as S 1 2 -modules and further restricted as modules over the Cartan subalgebra H are free of rank 2. We determine the necessary and sufficient conditions for these modules being simple, as well as determining the necessary and sufficient conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In [5], U(h)modules over the basic Lie superalgebras were investigated, which showed that osp(1|2n) is the only basic Lie superalgebra that admits such modules. The U(h)-free modules on some infinite-dimensional Lie superalgebras such as super-BMS 3 algebras, super-Virasoro algebras, untwisted N = 2 super conformal algebras were respectively studied in [3,21,22]. The aim of the present paper is to classify such modules for the twisted N = 2 superconformal algebras, and we further investigate the relevant twisted modules and weight modules.…”
Section: Introductionmentioning
confidence: 99%
“…In [5], U(h)modules over the basic Lie superalgebras were investigated, which showed that osp(1|2n) is the only basic Lie superalgebra that admits such modules. The U(h)-free modules on some infinite-dimensional Lie superalgebras such as super-BMS 3 algebras, super-Virasoro algebras, untwisted N = 2 super conformal algebras were respectively studied in [3,21,22]. The aim of the present paper is to classify such modules for the twisted N = 2 superconformal algebras, and we further investigate the relevant twisted modules and weight modules.…”
Section: Introductionmentioning
confidence: 99%